Rules and Historical Sources of Asbab al-Nuzul: A Theoretical-Epistemological Critique - Ilahiyah, Musfiroh Nihlah; Sanuri, S (QiST: Journal of Quran and Tafseer Studies, 2025)
This study aims to look at the ideas and knowledge of how to use asbāb al-nuzūl in the work of Qur'an interpretation. The main focus in this article is to explore the principles behind asbāb al-nuzūl in Islamic scholarly interpretation. The discussion aims to challenge concerns regarding the legitimacy of accounts, the categorization of texts, and the correlation between written material and its historical environment. It analyzes how traditional scholars such as al-Wāḥidī, al-Suyūṭī, and Ibn Taymiyyah developed strategies to identify the motives behind certain verses; simultaneously, it will highlight how modern thinkers such as Nasr Hamid Abu Zayd and Fazlur Rahman provide more situational and adaptive interpretive approaches that align with current movements and societal trends. The method of this study uses a form of research called literature study which involves looking at old and new books and sources. This article intends to question the belief that asbāb al-nuzūl is exclusively related to past events. Instead, it argues that certain reasons are constructs shaped by society, representing the first Muslim community's interpretive understanding of the verse that sought to adapt the verse's contested meaning to the challenges of the times. In addition, this article will also shed light on important rules in asbāb al-nuzūl studies, including al-'ibrah bi 'umūm al-lafẓ lā bi khuṣūṣ al-sabab and the tension between lafzi and sababī methods. The result shows that a lot of asb b reports are more about how to read and interpret than to tell true history The end says that today we need to put classic ideas with modern ways of understanding together.